Quantum walks of kicked Bose-Einstein condensates - Groiseau, Caspar; Gresch, Alexander; Wimberger, Sandro (Journal of physics. A, Mathematical and theoretical, 2018)
We analytically investigate the recently proposed and implemented discrete-time quantum walk based on kicked ultra-cold atoms. We show how the internal level structure of the kicked atoms leads to the emergence of a relative light-shift phase immediately relevant for the experimental realization. Analytical solutions are provided for the momentum distribution for both the case of quantum resonance and the near-resonant quasimomenta.